Therapeutic immunization protects dopaminergic neurons in a mouse model of Parkinson's disease - Benner, Eric J. (National Academy of Sciences, 2004)
Degeneration of the nigrostriatal dopaminergic pathway, the hallmark of Parkinson's disease, can be recapitulated in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-intoxicated mice. Herein, we demonstrate that adoptive transfer of copolymer-1 immune cells to MPTP recipient mice leads to T cell accumulation within the substantia nigra pars compacta, suppression of microglial activation, and increased local expression of astrocyte-associated glial cell line-derived neurotrophic factor. This immunization strategy resulted in significant protection of nigrostriatal neurons against MPTP-induced neurodegeneration that was abrogated by depletion of donor T cells. Such vaccine treatment strategies may provide benefit for Parkinson's disease.